Letter to the Editor: Only Ostensibly Anomalous - Dossey, Larry (Journal of Scientific Exploration, 2010)
I read with fascination Adrian Parker's excellent review (Parker, 2010) of Archie Roy's The Eager Dead: A Study in Haunting (Roy, 2008). Parker cites an example from the 1974 book The Challenge of Chance (Hardy, Harvie, & Koestler, 1974), in which co-author Arthur Koestler states that several top-secret codewords for the 1944 D-Day invasion showed up in crossword puzzles in The Daily Telegraph immediately prior to the military operation. Subsequent events not mentioned by Parker shed light on this remarkable scenario, which is a cautionary tale for anyone investigating ostensibly anomalous phenomena.